FREQUENCY OF ACUTE KIDNEY INJURY AMONG PATIENTS UNDERGOING CORONARY ANGIOGRAPHY828 - Sajid Khan (Army Medical College Rawalpindi, 2020)
Objective: To determine the frequency of acute kidney injury among patients undergoing coronary angiography.